If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12a + -323 = 12 Reorder the terms: -323 + 12a = 12 Solving -323 + 12a = 12 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '323' to each side of the equation. -323 + 323 + 12a = 12 + 323 Combine like terms: -323 + 323 = 0 0 + 12a = 12 + 323 12a = 12 + 323 Combine like terms: 12 + 323 = 335 12a = 335 Divide each side by '12'. a = 27.91666667 Simplifying a = 27.91666667
| 20x=25x | | 3(6b-5)-3(2-6b)= | | (-5)+1= | | 4(x+6)=(x+6)+5x+(3x+3) | | 8x-10+(-2x)+6=20 | | -0.8(1+2x)=2 | | -8+4x-9x+2=24 | | 2(3a-2)=-8 | | m-68.7=-16.1 | | 3r-2(4r-1)= | | X^3-324x= | | 10+5(2-2)=4z+1 | | 6x^2-11x-7=3 | | X^3-324=0 | | (5x+8)(x-9)=0 | | 8r-4(7-5r)= | | 15n+7=12n+12 | | .69+.19t=2.24t-.94 | | 1-0.4y=7 | | 8b-11b-3a-8a-10= | | (X+2)(x-5)(x-3+2i)(x-3-2i)=0 | | 8b-11b-8-3a-10= | | 8xy=10 | | 4(w+1)=25 | | y-42=-28 | | (2-y^5)(2+y^5)= | | x^3-60=x | | 111=144+11 | | 1=63tan(6x+5)-8 | | 4(3x+1)-5x=6+5x-2 | | 4=0.4(3d+5) | | 111=25+11 |